2010
DOI: 10.1111/j.1465-7295.2010.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effectiveness of Regulation and Pro‐social Emotions to Enhance Cooperation: Experimental Evidence From Fishing Communities in Colombia

Abstract: Abstract:This paper presents the results from a series of framed field experiments conducted in fishing communities off the Caribbean coast of Colombia. The goal is to investigate the relative effectiveness of exogenous regulatory pressure and pro-social emotions in promoting cooperative behavior in a public goods context. The random public revelation of an individual's contribution and its consequences for the rest of the group leads to significantly higher public good contributions and social welfare than re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…We implement four different treatments, namely: disclosure of negative information enforced through feelings of shame; disclosure of positive information driven by social esteem and pride; environmental regulation; and a treatment without any intervention. Our experimental design goes beyond previous field and lab experiments by presenting a test on the relative effectiveness of positive and negative information disclosure in the same setting; to our knowledge, others have focused on introducing only one of the two interventions (e.g., Maier-Rigaud et al, 2010;Lopez et al, 2009) or used disclosure experiments with approval and disapproval mechanisms operating at the same time (e.g., Rege and Telle, 2004;Martinsson and Villegas-Palacio, 2010).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We implement four different treatments, namely: disclosure of negative information enforced through feelings of shame; disclosure of positive information driven by social esteem and pride; environmental regulation; and a treatment without any intervention. Our experimental design goes beyond previous field and lab experiments by presenting a test on the relative effectiveness of positive and negative information disclosure in the same setting; to our knowledge, others have focused on introducing only one of the two interventions (e.g., Maier-Rigaud et al, 2010;Lopez et al, 2009) or used disclosure experiments with approval and disapproval mechanisms operating at the same time (e.g., Rege and Telle, 2004;Martinsson and Villegas-Palacio, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Contributions increased from 34.4% in the treatment without disclosure and approval possibilities, to 68.2% in the approval condition. Lopez et al (2009), in a framed field experiment with coastal communities using a standard linear public goods game, randomly reveal one member out of the five-person group and find that contributions to the public good increase from 14.6% without random revelation to 20.2% when the contribution is revealed. Barr (2001) obtained similar results in rural communities in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of the related literature has tested the impact of different regulations, both endogenous and exogenous, with ambiguous results with respect to monitoring levels and the size of punishment. SeeCardenas et al (2000Cardenas et al ( , 2002,Cardenas (2003),Cardenas (2004),Cardenas and Ostrom (2004),Lopez et al (2010), Velez et al (2009), Ostrom et al (1994,Rodríguez-Sickert et al (2008).…”
mentioning
confidence: 95%
“…In this way, forest depletion is prevented and, consequently, there is always a sufficient amount of trees to further satisfy the agents. The interplay among endogenous and exogenous institutions and enforcement, as is shown in the model, also reflects recent findings by Ostrom (2010:69) Lopez et al (2009) found that letting subjects know how their decisions affected the group in framed field experiments and allowing informal sanctions was more effective than externally imposed regulation." http://www.ecologyandsociety.org/vol19/iss1/art35/ Similar considerations can also be seen in the work of Baland and Platteau (1996), who state that external sanction systems are often necessary because of deficiencies of local enforcement mechanisms.…”
Section: Resultsmentioning
confidence: 51%